Peran financial technology LinkAja pada mahasiswa di Kota Malang - Vira Anandha; Imam Mukhlis (Universitas Negeri Malang, 2022)
Abstract One of the contactless payment phenomena in Indonesia is progressing rapidly with the presence of various types of digital payments, which has gained popularity among the community. Bank Indonesia provides a QR Code payment standard through server-based electronic money applications. This relatively speedy technological progression is followed by technological developments in the financial sector with the term Financial Technology (Fintech). Several Payment System Service Providers (PJSP) have obtained QRIS approval for the Non-Bank category, one of which is LinkAja, which supports the BI program. This study aims to determine the roles, functions, and benefits of digital payment systems among students in Malang City, as well as deepen the knowledge and behavior of students as application users. The research method used in this research is qualitative research. The study results show that LinkAja's features and services are helpful for students' daily activities. LinkAja's also collaborates with universities, providing booth services in several locations, along with cooperating with various platforms providing transportation services, lifestyle, and daily necessities, such as in traditional markets, merchants in malls, MSME players in Malang City to expand the distribution of usage non-cash transactions to create transactions that are safe, easy, practical, and structured. Abstrak Salah satu fenomena contactless payment di Indonesia saat ini berkembang cukup pesat dengan hadirnya berbagai macam jenis pembayaran digital yang menjadi trend bagi masyarakat. Bank Indonesia menyediakan standar pembayaran QR Code untuk pembayaran melalui aplikasi uang elektronik berbasis server. Perkembangan teknologi yang cukup pesat diikuti dengan perkembangan teknologi pada bidang keuangan dengan istilah Financial Technology (Fintech). Beberapa Penyelenggara Jasa Sistem Pembayaran (PJSP) yang telah memperoleh perjetujuan QRIS kategori Non Bank salah satunya LinkAja yang mendukung program BI, Penelitian ini bertujuan untuk mengetahui peran, fungsi, dan manfaat dari sistem pembayaran digital pada kalangan mahasiswa di Kota Malang serta memperdalam pengetahuan dan perilaku mahasiswa sebagai pengguna aplikasi.Metode penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif. Hasil penelitian menunjukan fitur dan layanan LinkAja bermanfaat bagi mahasiswa untuk kegiatan sehari-hari. Dengan upaya LinkAja melalui bekerjasama dengan universitas, menyediakan layanan booth di beberapa lokasi, kerjasama dengan berbagai platform penyedia jasa layanan transportasi, lifestyle, kebutuhan sehari-hari seperti di pasar tradisional, merchant di dalam mall, pelaku UMKM di Kota Malang dengan tujuan memperluas sebaran penggunaan transaksi non tunai agar tercipta transaksi yang aman, mudah, praktis, dan terstruktur.